The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Martin, Emily A. (2019)
Fil: Martin, Emily A. University of Wurzburg. Biocenter. Department of Animal Ecology and Tropical Biology; Alemania.